ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA SMP PADA MATERI ARITMATIKA SOSIAL DITINJAU DARI LITERASI MATEMATIKA SISWA - Halidin S.Pd., M.PMat; Chairuddin Chairuddin; Indra Purnomo (EMTEKA: Jurnal Pendidikan Matematika, 2023)
This study aims to identify the analysis of junior high school students' mathematical reasoning abilities on social arithmetic material in terms of students' mathematical literacy. the research method used is descriptive qualitative research. Sampling using porposive sampling technique. The sample in this study consisted of 31 class VII students of SMP Negeri 1 Tirawuta. The research instrument used was a test in the form of a description of mathematical reasoning abilities consisting of 4 questions, and interviews. The results showed that in terms of students' mathematical literacy. Based on 31 students in class VII A, it was found that the frequency of the high-level literacy category was 4 students with a percentage of 13%, the frequency for the medium-level literacy category was 9 students with a percentage of 29%, and the frequency for the category low-level literacy, namely 18 students with a percentage of 58%, from 31 students in class VII A, it was found that the frequency of the high-level reasoning category was 4 students, the frequency for the medium-level reasoning category was 9 students, and the frequency for the low-level category was 18 students, and Mathematical reasoning abilities in terms of students' mathematical literacy, namely 4 students with high levels of mathematical literacy have high levels of mathematical reasoning abilities, 10 students with moderate levels of mathematical literacy have moderate levels of mathematical reasoning abilities, and 18 students with low levels of mathematical literacy have pen skills. low-level mathematical solutions.